Strategi Meningkatkan Minat Beli melalui Budaya Ngopi Sebagai Gaya Hidup: Studi Fenomenologi Pada Kopi Kenangan Signature Mal Senayan City – Jakarta - Rachmat, Ikbal; Ardiyanti, Handrini; Silitonga, Kornelius Maranatha (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
This research explores the strategy of enhancing purchase interest through coffee culture as a lifestyle, focusing on a phenomenological study. The aim is to understand how coffee culture influences consumer behavior and preferences in choosing coffee shops, particularly examining Kopi Kenangan Signature in comparison to Starbucks. Through in-depth interviews and observations, the study delves into how coffee consumption at Kopi Kenangan Signature becomes a routine or habit for consumers, and how this practice adds meaning to their daily lives. Additionally, the influence of religious values on consumer preferences is analyzed, particularly in the context of Indonesia, where religious values play a significant role in consumer decision-making. The findings reveal that Kopi Kenangan Signature successfully differentiates itself from competitors by aligning with local values, traditions, and religiosity, thus attracting consumers who prioritize these aspects in their coffee shop choices. Overall, this study sheds light on the importance of understanding coffee culture as a lifestyle in crafting effective marketing strategies to increase purchase interest.